THE SPEECH ACTS AND CONVERSATIONAL IMPLICATURE OF WISE'S THE SOUND OF MUSIC - Chusni Hadiati (University of Muhammadiyah Purwokerto, 2009)
The conversation's implicatures as the impact of the violation of the cooperative principle's maxims of Grice (1975) can be classified into the speech act category of Searle (1975). The movie